Fear and Challenges of Nursing Students Being in Hospital for Clinical Posting During the COVID-19 Pandemic: An Exploratory Survey - Rana, Nimarta; Kalal, Nipin; Sharma, Suresh K. (Frontiers in Psychology, 2022)
Background: The world is facing unprecedented challenges in the face of a global pandemic (covid-19). The institutions resumed nursing students' clinical experiences as an earlier part of their curriculum which was transitioned to virtually delivered format due to global disaster. So working through this pandemic in hospital posting is challenging and fearful for nursing students. Aim of this study was to measure the fear of Covid -19 and challenges faced by nursing students when posted in hospital during Covid-19 pandemic. Methods: A web-based exploratory survey was conducted on 185 participants, during March- April 2021. Participants were selected through a web-based survey (Google form), by non- probability purposive sampling technique. The Fear of Covid-19 Scale and self-structured questionnaires with Likert scale were used to measure the fear of Covid -19 and challenges faced by nursing students when posted in hospital during Covid-19 pandemic respectively. Descriptive and inferential statistics were used for analysis of data with IBM SPSS version 27. Results: Significant number (61.1%) of participants had moderate fear of Covid- 19 infection and one third of them (28.1%) had mild fear and very few participants (10.8%) had extreme fear of Covid- 19 infection. Majority of participants (64.9%) were faced moderate challenges, 27.0% were faced high challenges and very few study participants (8.1%) were not faced any challenges when posted in hospital during Covid-19 pandemic. Fear due to Covid -19 is not associated with demographic variables but challenges faced due to Covid-19 is significantly associated with demographic variables such as the age, batch, and duration of clinical posting (p-value=0.01). Conclusion: Study data indicated that respondents reported fear of Covid-19 infection and also experienced variety of challenges in hospital posting during Covid -19 pandemic.